A Novel Antidiabetic Monomers Combination Alleviates Insulin Resistance Through Bacteria-Cometabolism-Inflammation Responses - Han, Lin; Zhao, Lin-Hua; Zhang, Ming-Liang; Li, Hua-Ting; Gao, Ze-Zheng; Zheng, Xiao-Jiao; Wang, Xin-Miao; Wu, Hao-Ran; Zheng, Yu-Jiao; Jiang, Xiao-Tian; Ding, Qi-You; Yang, Hao-Yu; et al. (Frontiers in Microbiology, 2020)
The present study sought to examine the therapeutic effect of a novel antidiabetic monomer combination (AMC) in treating type 2 diabetes mellitus (T2DM); while also elucidating the potential functional mechanism. Male C57BL/6J mice were fed a high-fat diet (HFD) for 12 weeks to establish T2DM. The AMC group showed significant reduction in weight, fasting blood glucose (FBG), serum total cholesterol (TC) and low density lipoprotein cholesterol (LDL-C), and experienced reduced insulin resistance based on oral glucose tolerance testing (OGTT) and hyperinsulinemic-euglycemic clamp testing (“gold standard” for determining in vivo insulin sensitivity). Further, AMC restored the altered intestinal flora by increasing the abundance of the beneficial bacteria Akkermansia, and decreasing the number of harmful bacteria, including Bacteroides, Odoribacter, Prevotella 9, Alistipes, and Parabacteroides. Components of the host-microbial metabolome were also significantly changed in the AMC group compared to the HFD group, including hydroxyphenyllactic acid, palmitoleic acid, dodecanoic acid, linoleic acid, and erucic acid. Furthermore, AMC was found to inhibit inflammation and suppress signaling pathways related to insulin resistance. Lastly, spearman correlation analysis revealed relationships between altered microbial community and co-metabolite levels, co-metabolites and inflammatory cytokines. Hence, the potential mechanism responsible for AMC-mediated alleviation of insulin resistance was suggested to be involved in modulation of bacteria-cometabolism-inflammation responses.